Connection, meaning, and distraction: A qualitative study of video game play and mental health recovery in veterans treated for mental and/or behavioral health problems. (November 2018) - Colder Carras, Michelle; Kalbarczyk, Anna; Wells, Kurrie; Banks, Jaime; Kowert, Rachel; Gillespie, Colleen; Latkin, Carl
Abstract: Rationale: Mental and behavioral health recovery includes concepts related not just to symptom improvement, but also to participating in activities that contribute to wellness and a meaningful life. Video game play can relieve stress and provide a way to connect, which may be especially important for military veterans. Objective: We examined how military veterans used video game play to further their mental and behavioral health recovery by conducting an exploratory thematic analysis of the gaming habits of 20 United States military veterans who were in treatment for mental or behavioral health problems. Method: We conducted semi-structured interviews in 2016 and used a framework analytic approach to determine salient themes linking video gaming to mental and behavioral health recovery. Results: Veteran participants reported that video games helped not only with managing moods and stress, but also with three areas related to other aspects of recovery: adaptive coping (e.g. distraction, control, symptom substitution); eudaimonic well-being (confidence, insight, role functioning); and socializing (participation, support, brotherhood). Meaning derived from game narratives and characters, exciting or calming gameplay, and opportunities to connect, talk, and lead others were credited as benefits of gaming. Responses often related closely to military or veteran experiences. At times, excessive use of games led to life problems or feeling addicted, but some veterans with disabilities felt the advantages of extreme play outweighed these problems. Conclusion: Video games seem to provide some veterans with a potent form of "personal medicine" that can promote recovery. Although reasons and results of gaming may vary within and among individuals, clinicians may wish to discuss video game play with their patients to help patients optimize their use of games to support recovery. Highlights: We spoke with veterans in mental health treatment about their video game play. Many veterans used games to connect to others, but some felt play was isolating. Video game play also supported adaptive coping and eudaimonic well-being. Several veterans described feeling addicted to games presently or in the past. For some veterans, video games may be "personal medicine" that promotes recovery.